Multilocus sequence typing of clinical and colonizing isolates of Acinetobacter baumannii and comparison with the world isolates - Jyoti Choudhary; Malini Shariff (BMC Microbiology)
Abstract Objectives To establish the epidemiological correlation between the study isolates, Indian and World isolates of Acinetobacter baumannii by performing Multilocus Sequence typing. Materials and methods A total of 181 isolates (Sputum (n = 116), lower respiratory tract other than sputum (n = 36), upper respiratory tract (n = 20), Environment (medical) (n = 4), and Blood (n = 5) of Acinetobacter baumannii were retrieved from our repository. DNA was isolated and Multilocus Sequence Typing was performed according to the Pasteur scheme. The amplified fragments were sequenced by outsourcing, and the locus and the sequence types were determined as given in the PUBMLST site. The clonal complexes were assigned using eBURST. Results and conclusion Of the 181 isolates, 20 were colonizers and 4 were from hospital environments. All the study isolates were multidrug-resistant (MDR) and 4 of them were extensively drug-resistant (XDR). 23 sequence types were unique and were assigned new sequence types. Among them, 2125 (n = 12), an SLV (Single Locus Variant) of 2, was the commonest followed by 2126 (n = 2) which was a DLV (Double Locus Variant) of 2 and an SLV of 2125. Others were singletons. Among the known STs, 149 (n = 72) was the commonest followed by ST 2 (n = 62) & 415 (n = 5), ST 10 (n = 4), ST 15, ST622 and ST1482 (3 each). ST149 had 1SLV ST1482 (n = 3). ST 2 has 5 SLVs (415, 1555, 2125, 2128, & 2131, and 2 DLVs (2130 & 2126). eBURST analysis of the study isolates showed three groups: Group I (86 isolates) with ST 2 as the primary founder, group II (6 isolates) and group III (79 isolates) with ST 149 as the primary founder. All the other 11 isolates were singletons. There was no difference in antimicrobial sensitivity or sequence types of clinical and colonizing isolates. The sequence types of study isolates were compared to the world isolates in the PUBMLST database. To conclude, MLST is an important tool for establishing isolates’ phylogenetic relationships. Acinetobacter baumannii being an important nosocomial pathogen should be routinely screened for the frequent changes in the sequence types to demonstrate the emerging resistance patterns and other changes.